2012
DOI: 10.1163/156853812x638518
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pine invasion on anurans assemblage in southern Brazil coastal ponds

Abstract: The destruction of wetlands due to afforestation areas is a common activity in temperate and subtropical regions in Southern America. The expansion of pine in the Coastal Plain of Southern Brazil is out of control and its impacts on aquatic biodiversity are little known. We tested the following hypotheses: the pine occurrence diminishes the anuran richness and abundance in ponds and it changes the anuran composition; the beta-diversity between pine and native grassland matrix ponds (natural ponds) is determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 44 publications
0
27
0
4
Order By: Relevance
“…In southern Brazil, 90% of the wetland systems have already been lost mainly due to agriculture, and the remaining ones are still at high risk due to the expansion of rice fields and exotic Eucalyptus and pine plantation . Studies conducted in wetlands of LPNP have shown that pine plantation changed the hydroperiod of wetlands causing a negative effect on macrophytes (Rolon et al 2011), macroinvertebrates (Stenert et al 2012), amphibians (Machado et al 2012), and probably on rivulid populations.…”
Section: Discussionmentioning
confidence: 99%
“…In southern Brazil, 90% of the wetland systems have already been lost mainly due to agriculture, and the remaining ones are still at high risk due to the expansion of rice fields and exotic Eucalyptus and pine plantation . Studies conducted in wetlands of LPNP have shown that pine plantation changed the hydroperiod of wetlands causing a negative effect on macrophytes (Rolon et al 2011), macroinvertebrates (Stenert et al 2012), amphibians (Machado et al 2012), and probably on rivulid populations.…”
Section: Discussionmentioning
confidence: 99%
“…Os estudos envolvendo ecologia de comunidades de anuros existentes no Bioma Pampa, historicamente, estão concentrados na região da Planície Costeira (e.g., colomBo et al, 2008;maltcHik et al, 2008;moreira et al, 2008;macHado & maltcHik, 2009;macHado et al, 2012;oliveira et al, 2013), enquanto as fisionomias campestres interioranas permaneceram pouco exploradas exceto pelos estudos de santos et al (2008) na Depressão Central, BotH et al (2011) na Serra do Sudeste e di- Bernardo et al (2002) na região da Campanha. Apesar do crescente número de estudos, o conhecimento acerca dos padrões de composição, diversidade e distribuição espacial dos anuros desta região ainda são escassos.…”
unclassified
“…The population in this study is one of the few currently known in Brazil (see Iop et al, 2009;Lucas and Marocco, 2011;Lucas and Garcia, 2011;Lipinski et al, 2012;Bastiani and Lucas, 2013). Fragmentation and isolation of the interior Atlantic Forest, expansion of hydroelectric projects in the region, and land and soil conversion for agricultural (Câmara, 2003;Bonai et al, 2009;Ternus et al, 2011) and silvicultural projects (Machado et al, 2012) may promote isolation of H. curupi populations. Such isolation increases the risk of extinction from inbreeding, genetic and demographic stochasticity, and vulnerability to diseases such as chytridiomycosis (Toledo et al, 2006).…”
Section: Discussionmentioning
confidence: 89%